PENILAIAN KESESUAIAN LINGKUNGAN SOSIAL MASYARAKAT DALAM EVALUASI LAHAN TPA SAMPAH - Zetly E. Tamod (EKOTON, 2014)
Evaluating the land for Waste TPA (disposal site) has been conducted through comparing the physical land and public response in which the result will be grouped in three classes of compatibility: compatible, relatively compatible, and incompatible. Results of land compatibility assessment constitute a basis to determine (recommend) the location of Waste TPA. Social environment compatibility rate must be included within the measurement together with public response on planning or evaluating stages of Waste TPA location. This assessment emphasizes on education or knowledge rate and public perception on Waste TPA, health rate, and the role. The results, hence, enter into three classes of responses: positive, neutral, and negative.